Dilute sulfuric acid pretreatment for cellulose recovery from sawdust - Rozialfi, Alwaner (2010)
Cellulose has much function in producing valuable product such as bioethanol that has the same function with the crude oil and produce using cheaper and abundant raw material (biomass). The biomass that has been used in this research is sawdust. In order to recover cellulose from sawdust, it is necessary to treat the sawdust using dilute sulfuric acid pretreatment as to remove the lignin and hemicelluloses that bonding the cellulose structure. Compared with the untreated sawdust, 3.4 g/l glucose was dissolved from the cellulose, whereas hemicelluloses which are xylose and arabinose in pre-treated sawdust decreased to 2.5 g/l and 6.8 g/l, respectively. The results of infrared spectra (IR) and scanning electron microscope (SEM) analysis also showed that the structure and the surface of the sawdust were changed through pretreatment and crystalline cellulose in sawdust pretreated was disrupted. The maximum cellulose recovery of sawdust was achieved at a sulfuric acid concentration of 4 % and pretreatment time of 120 minutes.